Pupil light reflex dynamics in Parkinson’s disease - Tsitsi, Panagiota; Nilsson, Mattias; Waldthaler, Josefine; Öqvist Seimyr, Gustaf; Larsson, Olof; Svenningsson, Per; Markaki, Ioanna (Frontiers in Integrative Neuroscience, 2023)
Introduction Visual disturbance is common symptom in Parkinson’s disease (PD), and defective pupil light reflex (PLR) is an anticipated contributing factor that may be associated to the presence of autonomic dysfunction, which is a common non-motor feature of PD. Studies investigating the intercorrelation between PLR and dysautonomia in PD are limited. Methods The aim of this study was to investigate differences of PLR parameters, measured by eye-tracker, between patients with PD, with and without signs of dysautonomia, and healthy controls (HC). In total, 43 HC and 50 patients with PD were recruited and PLR parameters were measured with Tobii Pro Spectrum, during a long (1,000 ms) and a short (100 ms) light stimulus. Presence of orthostatic hypotension (OH) was used as proxy marker of dysautonomia. Linear mixed-effects model and non-parametric comparative statistics were applied to investigate differences among groups. Results Peak constriction velocity was slower in PD compared with HC, after adjustment for age and sex in the mixed model, and the difference was greater in the subgroup of PD with OH (unadjusted). Dilation amplitude and velocity were also gradually slower in HC vs. PD without OH vs. PD with OH (unadjusted for confounders). In the mixed model, age was significant predictor of dilation response. Discussion Our results support previous observations on defective PLR in PD, evaluated with eye-tracker, and show a possible association with autonomic dysfunction. Further studies with more patients and rigorous evaluation of autonomic dysfunction are needed to validate these findings.